2014
DOI: 10.1186/1556-276x-9-95
|View full text |Cite
|
Sign up to set email alerts
|

Seed/catalyst-free vertical growth of high-density electrodeposited zinc oxide nanostructures on a single-layer graphene

Abstract: We report the seed/catalyst-free vertical growth of high-density electrodeposited ZnO nanostructures on a single-layer graphene. The absence of hexamethylenetetramine (HMTA) and heat has resulted in the formation of nanoflake-like ZnO structure. The results show that HMTA and heat are needed to promote the formation of hexagonal ZnO nanostructures. The applied current density plays important role in inducing the growth of ZnO on graphene as well as in controlling the shape, size, and density of ZnO nanostructu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 39 publications
4
34
0
Order By: Relevance
“…The overall reaction for nucleation was dependent on the deposition process to the cathode surface. Hence, considering the primary growth reaction of ZnO via ECD with Zn(NO 3 ) 2 (Zn(NO3)26H2normalO) and KCl as reagents, they can be broken down in the chemical reactions listed below [45,46,47,48]:Zn(NO3)2 + 2 KCl  ZnCl2 + 2 KNO3…”
Section: Growth Mechanism Discussion and Further Annealingmentioning
confidence: 99%
“…The overall reaction for nucleation was dependent on the deposition process to the cathode surface. Hence, considering the primary growth reaction of ZnO via ECD with Zn(NO 3 ) 2 (Zn(NO3)26H2normalO) and KCl as reagents, they can be broken down in the chemical reactions listed below [45,46,47,48]:Zn(NO3)2 + 2 KCl  ZnCl2 + 2 KNO3…”
Section: Growth Mechanism Discussion and Further Annealingmentioning
confidence: 99%
“…Up to now, we have reported the shape controllability of vertically aligned ZnO NRs prepared by the CBD techniques using zinc chloride (ZnCl 2 ) and zinc acetate dihydrate [Zn(CH 3 COO) 2 · 2H 2 O] as source materials and their photoluminescence (PL) properties [29]. We have also reported the successful growth of vertically aligned ZnO NRs on graphene/glass substrates by ED [30]. It was also confirmed that the optical properties and diameters of the NRs can be effectively controlled by the current density during the deposition process [31].…”
Section: Introductionmentioning
confidence: 96%
“…Li et al reported on the synthesis of ZnO nanoparticles on Si substrates with and without an Au catalyst [16]. Recently, we report the growth of ZnO nanostructures on seed/ catalyst-free substrates by introducing graphene as the template layer using both electrochemical and hydrothermal processes [14,23,26]. Up to date, there is no report on the formation of a ZnO continuous film structure on a ZnO-seeded substrate using liquid-phase methods.…”
Section: Introductionmentioning
confidence: 97%
“…Liquid-phase techniques such as hydrothermal and electrochemical processes have been widely used to grow ZnO structures on ZnO-seeded substrates [7,11,17,[19][20][21], catalyzed substrates [22], or seed/catalyst-free substrates [14,19,21,23]. Generally, the grown ZnO structures on the ZnO-seeded substrates are mostly in the form of onedimensional (1D) nanostructures [7,9,20,21,24,25] due to the nature of chemical reaction of liquid-phase techniques and also due to the small grains and rough surfaces of ZnO seed layers prepared by the sputtering method [7,20,21] or other deposition techniques [9,24,25].…”
Section: Introductionmentioning
confidence: 99%